Comparative evaluation of 4 commercial modified‐live porcine reproductive and respiratory syndrome virus (PRRSV) vaccines against heterologous dual Korean PRRSV‐1 and PRRSV‐2 challenge. Issue 4 (21st May 2020) - Oh, Taehwan; Park, Su‐Jin; Cho, Hyejean; Yang, Siyeon; Ham, Hee Jin; Chae, Chanhee
Abstract: Background: Four commercial porcine reproductive and respiratory syndrome virus (PRRSV) modified‐live vaccines (MLV) was compared to protect growing pigs against dual challenge of PRRSV‐1 and PRRSV‐2. Methods: Two of the vaccines were based on PRRSV‐1, and two on PRRSV‐2. A total of 72 PRRSV‐naïve pigs were divided into six groups (12 pigs/group). Results: Two PRRSV‐1 MLV‐vaccinated and two PRRSV‐2 MLV‐vaccinated groups reduced significantly ( p  < .05) genomic copies of PRRSV‐1 in their sera compared to the unvaccinated challenged group. Two PRRSV‐2 MLV‐vaccinated groups reduced significantly ( p  < .05) fewer genomic copies of PRRSV‐2 in their sera whereas two PRRSV‐1 MLV‐vaccinated groups were unable to reduce genomic copies of PRRSV‐2 compared to unvaccinated challenged groups. Two PRRSV‐1 MLV‐vaccinated groups induced a stronger PRRSV‐1 specific IFN‐γ‐SC response, while two PRRSV‐2 MLV‐vaccinated groups induced a stronger PRRSV‐2 specific IFN‐γ‐SC response. Two PRRSV‐2 MLV‐vaccinated groups showed significantly ( p  < .05) lower mean macroscopic and microscopic lung lesion scores compared to two PRRSV‐1 MLV‐vaccinated groups. Conclusions: These data demonstrated that two PRRSV‐2 vaccines were efficacious and exhibited similar protection while, two PRRSV‐1 vaccines were largely ineffective against the dual challenge. Abstract : Four commercial porcine reproductive and respiratory syndrome virus (PRRSV) modified‐live vaccines (MLV) was compared to protect growing pigs against dual challenge of PRRSV‐1 and PRRSV‐2. These study demonstrated that two PRRSV‐2 vaccines were efficacious and exhibited similar protection while, two PRRSV‐1 vaccines were largely ineffective against the dual challenge.